STUDY OF CLEAR AIR TURBULENCE IN JAVA SEA USING NUMERICAL WEATHER PREDICTION WRF (WEATHER RESEARCH AND FORECASTING) - ARIF MUNANDAR (NIM : 22412307); Pembimbing : Dr. Nurjanna Joko Trilaksono, MUHAMMAD
Clear Air Turbulence (CAT) became one of the concerns in aviation because can reduce the comfort, loss of fuel and injure passengers. Research on CAT has been widely applied in various regions either through observation and numerical models. For the tropics, research on CAT still very limited so need study further. The study was conducted by using a numerical simulation using the Weather Research and Forecasting model of ARW (WRF-ARW) because of the limitations of observational data and the problems are quite complex. The turbulences data comes from Pilot Weather Reports (PIREPs) obtained from Air Traffic Controller (ATC). Terms boundary and initial conditions for the simulation model using the data NCEP FNL (Final Analysis). Output models have been validated using radiosonde data and image watervapour MTSAT where the results are considered representative of actual conditions. The selection of horizontal resolution for the best match. Retrieved ten km horizontal resolution for further analysis. The results of simulation models WRF-ARW values obtained Richardson Number (Ri) is less than one in the region reported the occurrence of CAT. This is due to the presence of wind shear due to changes in wind speed vertically on the site. To see the effect of the number of simulated altitude of the vertical height of the number performed. The results obtained indicate that the horizontal resolution of ten miles both used to represent events CAT while setting the number of layers above denser over CAT represent events.